Jury Rigging and Supply Network Design: Evolutionary "Tinkering" in the Presence of Unknown‐Unknowns. Issue 1 (22nd September 2017) - Kauffman, Stuart; Pathak, Surya D.; Sen, Pradyot K.; Choi, Thomas Y.
Abstract : Nobel laureate François Jacob wrote often about evolution as "tinkering" in which parts and processes alone or together in cells and organisms were co‐opted for new functional purposes. Such behavior remains unexamined concerning how adaptive systems succeed in biology, supply networks, the economy, and beyond. In the presence of Unknown‐Unknown events (Unk‐Unks) that have no prior occurrences and are evident only in their realizations, the design of supply networks must allow for developing adaptive capabilities at the firm‐level. When performed right, such organic development in the supply network would mimic a biological phenomenon of tinkering and natural selection. We describe enabling such adaptive processes as jury rigging. We discuss how firms could design their supply networks and organize their supply network ex‐ante that enables the network members to respond to Unk‐Unks in an innovative way through jury rigging of their relationships. Development of such jury rigging capabilities requires integrative suppliers with deep embedded relationships, enabled through appropriate incentives that include incomplete contracts with the suppliers and sharing of unspecified decision rights.